A Novel Prokaryote-Type ECF/ABC Transporter Module in Chloroplast Metal Homeostasis - Voith von Voithenberg, Lena; Park, Jiyoung; Stübe, Roland; Lux, Christopher; Lee, Youngsook; Philippar, Katrin (Frontiers in Plant Science, 2019)
During evolution, chloroplasts, which originated by endosymbiosis of a prokaryotic ancestor of today’s cyanobacteria with a eukaryotic host cell, were established as the site for photosynthesis. Therefore, chloroplast organelles are loaded with transition metals including iron, copper, and manganese, which are essential for photosynthetic electron transport due to their redox capacity. Although transport, storage and cofactor-assembly of metal ions in chloroplasts are tightly controlled and crucial throughout plant growth and development, knowledge on the molecular nature of chloroplast metal-transport proteins is still fragmentary. Here we characterized the soluble, ATP-binding ABC-transporter subunits ABCI10 and ABCI11 in Arabidopsis thaliana, which show similarities to components of prokaryotic, multisubunit ABC transporters. Both ABCI10 and ABCI11 proteins appear to be strongly attached to chloroplast-intrinsic membranes, most likely inner envelopes for ABCI10 and possibly plastoglobuli for ABCI11. Loss of ABCI10 and ABCI11 gene products in Arabidopsis leads to extremely dwarfed, albino plants showing impaired chloroplast biogenesis and deregulated metal homeostasis. Further, we identified the membrane-intrinsic protein ABCI12 as potential interaction partner for ABCI10 in the inner envelope. Our results suggest that ABCI12 inserts into the chloroplast inner envelope membrane most likely with five predicted α-helical transmembrane domains and represents the membrane-intrinsic subunit of a prokaryotic-type, energy-coupling factor (ECF) ABC-transporter complex. In bacteria these multisubunit ECF importers are widely distributed for the uptake of nickel and cobalt metal ions as well as for import of vitamins and several other metabolites. Therefore, we propose that ABCI10 (as the ATPase A-subunit) and ABCI12 (as the membrane-intrinsic, energy-coupling T-subunit) are part of a novel, chloroplast envelope-localized, AAT energy-coupling module of a prokaryotic-type ECF transporter, most likely involved in metal ion uptake.